Digital financial literacy within the Telegram platform at the @sarjanacrypto community - Farabi, Muhammad Nabiel; Damayani, Ninis Agustini; Rodiah, Saleha (Jurnal Informatio, 2026)
Background: The crypto asset investment ecosystem on Telegram is characterised by extreme Information Velocity, which creates severe cognitive load, triggering irrational herding behaviour and exacerbating investor vulnerability to rampant misinformation.Purpose: This study analyses digital financial literacy as a cognitive defence mechanism against crypto misinformation within the Dark Social ecosystem of Telegram, specifically focusing on the @sarjanacrypto community.Methods: Employing a qualitative single-case study design, data were triangulated from online non-participatory observation, a thematic reduction of 3,974 archived Telegram messages, and in-depth interviews with seven informants spanning various market experiences.Results: Findings reveal how investors practice digital financial literacy to combat crypto misinformation. The results show that investors frequently engage in "Pseudo-DYOR" practices and suffer Situational Regression, in which even experienced individuals revert to impulsive System 1 processing during extreme market euphoria, resulting in an illusion of literacy and a false sense of security that leaves them highly vulnerable to manipulation.Conclusions: Digital financial literacy in high-velocity ecosystems operates as a reactive, evolutionary process rather than a linear educational outcome. Financial trauma acts as the primary catalyst, forcing investors to adopt independent verification. Practically, investor protection strategies must shift from normative dissemination to cultivating cognitive resilience and cross-platform verification habits.